Fecal microbiota transplantation improves hepatic steatosis induced by HFD in a mouse model associated with liver ILC1 regulation and indole-3-carbinol level - Hou, Peng-fei; Yao, Yu; Wu, Ying; Yu, Hong-tao; Qin, Yu; Yi, Long; Mi, Man-tian (Frontiers in Nutrition, 2025)
BackgroundThe prevalence of metabolic dysfunction-associated steatotic liver disease (MASLD) has increased worldwide. In recent years, fecal microbiota transplantation (FMT) has become an important promising method for the treatment of MASLD. However, the mechanism remains unclear.MethodsThe animal model with C57BL/6 male mice induced by high-fat diet (HFD) for 12 weeks has been introduced. Fecal microbiota and indole-3-carbinol (I3C) was given by oral gavage.ResultsOur study demonstrated that a 6-week healthy gut microbiota transplantation tended to ameliorate hepatic steatosis and reverse the decreased liver ILC1 induced by HFD. Interestingly, there was also a negative correlation between liver ILC1 and liver TG, TC level. Furthermore, the protective effect was associated with the elevated levels of serum indole-3-carbinol (I3C). Also, a I3C administration for 6 weeks improved liver steatosis and increased the frequency of liver ILC1 induced by HFD through aryl hydrocarbon receptor (AhR) activation. Moreover, I3C binds to the residues of ALA349, PHE348, LEU309, TYR316, PHE318 on AhR through hydrogen bonds, Π bonds, hydrophobic bonds which was proved by molecular docking.ConclusionTo conclude, our data demonstrated that FMT improved liver steatosis induced by HFD associated with liver ILC1 regulation and indole-3-carbinol level. The study highlighted the potential treatment value of FMT and microbiota-derived I3C in the MASLD treatment and regulation of liver ILC1 function.